Gandhi's Thoughts on Education in the Context of Religion - Bilimoria, Purusottama (Journal of Dharma, 1984)
In developing a framework that links Mahatma Gandhi's views on education in its most salient features with his overall thoughts on morality, culture and religion, I have admittedly encountered some difficulties, which I would like to mention at the very outset. One basic difficulty is presented by the ambivalence one finds in Gandhi's thought on this subject-matter, which is evident in the apparent gap between the ideal, in terms of which his views are couched, and the actual, in terms of which the ideal is to be realized in real life. This makes it difficult to determine how exactly one should approach the problematic.